Audit firms merger and audit market concentration / Hilwani Hariri ... [et al.] - Hariri, Hilwani; Che Ahmad, Ayoib; Abd. Rahman, Norshimah; Fauzee, Fairuz (Universiti Teknologi MARA, Perlis, 2006)
This study examined the impact of merger between Price Waterhouse and Coopers & Lybrand in 1998 on audit concentration in Malaysian audit market. The market share of publicly listed companies for audit firms before the merger (1997 and 1998) and post merger (1999, 2000 and 2001) for each of industry category were perused. Concentration ratio for the Big Four audit firms (CR4) and Herfindahl Index (HI4) were used as methods to identify the level of concentration. Result showed that merger did increase the concentration level of the audit market significantly.